Indigenous software for sizing large scale rooftop grid-connected photovoltaic systems in Malaysia / Shahril Irwan Sulaiman … [et al.] - Sulaiman, Shahril Irwan; Othman, Zulkifli; Zainuddin, Hedzlin; Osman, Muhammad Sukhri; Abg Abdullah, Dayang Nailul Munna (Research Innovation Business Unit, 2014)
This project presents an indigenous software for sizing large-scale rooftop-based grid-connected photovoltaic systems. The software which was developed in Visual Basic, enables the user to select a photovoltaic (PV) module and inverter so that the expected AC kWh energy output from the system could be maximized based on several site conditions such as solar irradiation profile, available roof space, inverter-to-PV array capacity ratio, tolerances, losses as well as efficiencies of components throughout the system. The site conditions are adjustable according to user’s experience and knowledge. During the sizing process, the dimensioning of PV array is conducted to match the input voltage and current limits of the inverter. Besides that, several techno-economic parameters such as annual energy output, Specific Yield, Performance Ratio, Roof Utilization Factor, and estimated income from Feed-In-Tariff scheme are calculated to complete overall sizing process.